Proof: Divide by 2
Let's prove the following theorem:
if the following are true:
- not (b = 0)
- not (2 = 0)
- not (b ⋅ 2 = 0)
then (a ⋅ 2) / (b ⋅ 2) = a / b
Proof:
Given
1 | not (b = 0) |
---|---|
2 | not (2 = 0) |
3 | not (b ⋅ 2 = 0) |
# | Claim | Reason |
---|---|---|
1 | (a / b) ⋅ 1 = a / b | (a / b) ⋅ 1 = a / b |
2 | 2 / 2 = 1 | 2 / 2 = 1 |
3 | (a / b) ⋅ (2 / 2) = a / b | if (a / b) ⋅ 1 = a / b and 2 / 2 = 1, then (a / b) ⋅ (2 / 2) = a / b |
4 | (a / b) ⋅ (2 / 2) = (a ⋅ 2) / (b ⋅ 2) | if not (b = 0) and not (2 = 0) and not (b ⋅ 2 = 0), then (a / b) ⋅ (2 / 2) = (a ⋅ 2) / (b ⋅ 2) |
5 | (a ⋅ 2) / (b ⋅ 2) = a / b | if (a / b) ⋅ (2 / 2) = (a ⋅ 2) / (b ⋅ 2) and (a / b) ⋅ (2 / 2) = a / b, then (a ⋅ 2) / (b ⋅ 2) = a / b |
Comments
Please log in to add comments